Filling the gaps in the distribution of an alien species: The case of the feather-legged fly Trichopoda pennipes (Diptera: Tachinidae) in the Western Palearctic - Kazilas, Christos; Demetriou, Jakovos; Kalaentzis, Konstantinos (ENTOMOLOGIA HELLENICA, 2020)
The feather-legged fly, Trichopoda pennipes (Fabricius, 1781), is a parasitoid species introduced in several European countries over the last decades. This study provides new records for the presence of the tachinid in Mediterranean and Black Sea coastal areas. Four individuals were observed by the authors in Greece and Cyprus (2015-2019) and 11 additional records of the fly in Albania, Cyprus, Greece, Russia, and Turkey (2011-2019) were obtained from citizen science platforms. We provide the first records of the species on the aforementioned countries, contributing in the expansion of the current distribution range of the species. Current and future hypothetical expansion scenarios, as well as potential ecological implications are presented and discussed.